Mutation spectrum and genotype-phenotype correlations in a large French cohort of MYH9-Related Disorders - Saposnik, Béatrice (BlackWell Publishing Ltd, 2014)
MYH9-Related Disorders are a group of rare autosomal dominant platelet disorders presenting as nonsyndromic forms characterized by macrothrombocytopenia with giant platelets and leukocyte inclusion bodies or as syndromic forms combining these hematological features with deafness and/or nephropathy and/or cataracts. They are caused by mutations in the MYH9 gene encoding the nonmuscle myosin heavy chain II-A (NMMHC-IIA). Until now, at least 49 MYH9 mutations have been reported in isolated cases or small series but only rarely in large series. We report the results of an 8-year study of a large cohort of 109 patients from 37 sporadic cases and 39 unrelated families. We have identified 43 genetic variants, 21 of which are novel to our patients. A majority, 33 (76.7%), were missense mutations and six exons were preferentially targeted, as previously published. The other alterations were three deletions of one nucleotide, one larger deletion of 21 nucleotides, and one duplication. For the first time, a substitution T>A was found in the donor splice site of intron 40 (c.5765+2T>A). Seven patients, four from the same family, had two genetic variants. The analysis of the genotype-phenotype relationships enabled us to improve the knowledge of this heterogeneous but important rare disease.